The implementation of the STEAM learning model in the Nahwu course at Universitas Muhammadiyah Malang - Nisa, Choirun; Muballigh, Ahmad; Fitriani, Laily (Abjadia : International Journal of Education, 2025)
Education in this era has a vision to connect technology, humans, and their needs, as life today is dominated by high-tech products. To support the success of Arabic language learning, several tools need to be studied, one of which is Nahwu, or as it is often referred to in linguistic studies, syntax. One of the efforts to achieve educational goals is to introduce something new in the learning process as a solution. This can be done through the application of STEAM (Science, Technology, Engineering, Arts, and Mathematics). The research used is descriptive qualitative, with research instruments such as observation, interviews, and documentation conducted in the Arabic Language Education Department at Universitas Muhammadiyah Malang. The results of this study indicate that the STEAM learning model in the Nahwu course at the Arabic Language Education Department can be applied, although some students are still not accustomed to learning using pre-tests and the short intervals between lessons, as they are used to Teacher Centerer learning. Regarding the project assignments given, the students were able to complete them thoroughly and on time for each group. Overall, the students' responses during the implementation of the STEAM learning model were very enthusiastic. Therefore, with the STEAM learning model, students were able to foster a high sense of curiosity, critical thinking, collaboration, creativity, and self-confidence.